Systematic Literature Review on Sustainable Value Chain Transformation of Arenga pinnata in Tropical Bioresource Systems - Abdul Samad Hiola; Marini Susanti Hamidun; Indra Gumay Febryano (Forest and Nature, 2026)
Aren (Arenga pinnata) has emerged as a multifunctional tropical species. It has the potential to contribute to sustainable value chain development, the circular bioeconomy, and rural livelihoods. Nevertheless, existing literature remains fragmented and addresses ecological, technological, and governance dimensions in isolation. This study systematically reviews the literature on the sustainable value chain transformation of A. pinnata within tropical bioresource systems. It identifies factors influencing its transition from a traditional multipurpose palm to a strategic bioresource platform. A systematic literature review was conducted through a structured process. The steps included search, screening, eligibility assessment, data extraction, and thematic synthesis. The review combined empirical studies with broader literature on circular bioeconomy, value chain restructuring, social sustainability, and governance. The analysis covered four thematic domains: upstream resource systems, midstream processing and upgrading, downstream diversification, and market or institutional alignment. The review shows that A. pinnata can drive transformative change. This is due to its multifunctionality, ecological adaptability, and diverse product pathways. Upstream research highlights its role in agroforestry, biodiversity-linked landscapes, and livelihood systems. Midstream studies identify opportunities for product stabilization, fermentation, and process improvement. Downstream investigations show promising use in thermoplastic starch, composites, functional biomaterials, and circular by-products. However, integration among these advances is weak. Technical innovation often outpaces commercialization and governance. Value distribution, coordination, and inclusion also remain underdeveloped. The study concludes that the sustainable transformation of A. pinnata requires integrating resource sustainability, technological upgrading, and market or institutional alignment. This review offers an integrated framework for understanding aren-based transformation and identifies priorities for future research on commercialization, circularity, and inclusive tropical bioresource development.